ChemInform Abstract: A Short and Efficient Synthesis of 5, 5′‐Bi‐1, 2, 3‐dithiazoles. Issue 19 (21st April 2016) - Konstantinova, Lidia S.; Bol'shakov, Oleg I.; Baranovsky, Ilia V.; Bogacheva, Anna M.; Strunyasheva, Vlada V.; Rakitin, Oleg A.
Abstract: The title dithiazoles are obtained by reaction of arylethanone oximes with S2 Cl2 followed by treatment with copper powder.